2021
DOI: 10.1016/j.ultsonch.2021.105540
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted depolymerization of kappa-carrageenan and characterization of degradation product

Abstract: Highlights First report on structural change in κ-carrageenan under ultrasonic condition. Sonication decreased the average molecular weight of κ-carrageenan. Sonication afforded minor modification in the structure of the κ-carrageenan repeating units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…As the Tg is critically relevant in specific pharmaceutical, cosmetic, or food applications [ 29 ], the control of the processing conditions allowed to deliver a set of gelling hybrid carrageenans, with gelling temperatures varying from 40 to 75 °C, thus satisfying a wide application spectrum. Different features can be determinant on these properties, including the average molecular weight and polydispersity [ 30 ], and both conventional and ultrasonic processing can alter the molecular weight of carrageenan [ 6 ]. The effect of ultrasound on depolymerization is well known; an example is the work by Tecson and coauthors, who observed a decrease in molecular weight of refined κ-carrageenan, attributable to the hydrolytic cleavage and scission along the chain, especially at the O-glycosidic bond [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As the Tg is critically relevant in specific pharmaceutical, cosmetic, or food applications [ 29 ], the control of the processing conditions allowed to deliver a set of gelling hybrid carrageenans, with gelling temperatures varying from 40 to 75 °C, thus satisfying a wide application spectrum. Different features can be determinant on these properties, including the average molecular weight and polydispersity [ 30 ], and both conventional and ultrasonic processing can alter the molecular weight of carrageenan [ 6 ]. The effect of ultrasound on depolymerization is well known; an example is the work by Tecson and coauthors, who observed a decrease in molecular weight of refined κ-carrageenan, attributable to the hydrolytic cleavage and scission along the chain, especially at the O-glycosidic bond [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Different features can be determinant on these properties, including the average molecular weight and polydispersity [ 30 ], and both conventional and ultrasonic processing can alter the molecular weight of carrageenan [ 6 ]. The effect of ultrasound on depolymerization is well known; an example is the work by Tecson and coauthors, who observed a decrease in molecular weight of refined κ-carrageenan, attributable to the hydrolytic cleavage and scission along the chain, especially at the O-glycosidic bond [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations